Argumentative trees. What it takes, what it leaves - Marianne Doury; Pierre Pilon (Argumentation et Analyse du Discours)
This paper analyzes five argumentation visualization software tools (MindMup, Rationale, bCisive, OVA, and MindManager) through the theoretical lens of O'Keefe's triple distinction between argument₁ (propositional content), making-an-argument (speech act) and argument₂ (argumentative interaction). Using examples from the play “Twelve Angry Men,” the study examines how these tools handle different dimensions of argumentation. While most tools effectively represent argument₁ structures, they struggle to capture the complexities of speech acts and interactive dynamics. The analysis reveals that visualization tools face inherent limitations in representing crucial aspects such as power relations, narrative force, and emotional dimensions of argumentative exchanges. Rather than viewing these limitations as mere technical constraints, the paper suggests reconsidering visualization tools as heuristic instruments illuminating specific aspects of argumentation.